A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar - Vences, Miguel; Hildenbrand, Andrea; Warmuth, Katharina M.; Andreone, Franco; Glaw, Frank (Zootaxa, 2018)
The subgenus Brygoomantis in the Madagascar-endemic genus Mantidactylus contains 12 nominal species but is in urgent need of taxonomic revision as many additional, genetically divergent but undescribed candidate species have been identified. We here take a first step towards a better resolution of this group by describing a new species, Mantidactylus schulzi sp. nov., occurring at the Tsaratanana and Manongarivo Massifs, differentiated in genetic, bioacoustic and sometimes morphological characters from its closest relatives. We show that upon detailed study, most species in Brygoomantis can be delimited by concordant differentiation of mitochondrial and nuclear DNA, and by bioacoustic and morphological differences. We flag this group of morphologically similar frogs as a test case where molecular data on historical type specimens by ancient DNA methods might be needed to reach a satisfying clarification of taxonomy and nomenclature. However, the status of the new species M. schulzi is not in doubt as it is morphologically distinct from most historical type specimens, and microendemic to a region in northern Madagascar from where no earlier names exist.